Modelagem e simulação das correlações de scale-up para o processo de flotação por ar dissolvido (fad) utilizando análise dimensional - Vasconcelos, Robson de Souza (2015)
The implantation costs of dissolved air flotation (DAF) pilot units require special strategies due to the lack of correlations between laboratory and industrial scale, as novel flotation methods have been considered strictly from an economic standpoint. In this sense, significant efforts have been made to describe and model a scale-up to the process of FAD, being necessary to design and validate a scale-up forecasting model to promote a change in the required scale. In this study a scale-up correlation for a pilot unit project was determined based on the analysis of dynamic similarity correlations involving the predominant phenomena of a dissolved air flotation (DAF) chamber used in separating and recovering oily water. With the aid of computational fluid dynamics and videos of microbubble and floc flow, inertia and gravity were identified as the predominant phenomena in a DAF chamber by the discrepancy between the average speeds of rise of microbubbles and flakes of 8.73 10-7 m/s and 1.17510-5 m/s, respectively. The simulations were performed using ANSYS software and measurements were made with the aid of a camera. The strategy described herein is simple and reduces the likelihood of future risks in scale-up investments.